Learning Qur’anic Arabic through interactive Web-based software: a pragmatic approach in language for specific purpose - Abdullah, Matin Saad; Pathan, Al-Sakib Khan (2013)
About 80 percent of the world's Muslim populations are non-native speakers of the Arabic language. Since ‎it ‎is ‎‎obligatory for all Muslims to recite the Qur'an in Arabic ‎during regular prayers, ‎an ‎extraordinary ‎‎social phenomenon has taken place ‎in some parts of the ‎Muslim ‎world: in schools, children are only taught the complex phonological rules of the ‎Arabic language ‎in ‎the ‎context of the Qur'an. This has given rise to a demographic segment of adult learners who are interested in a Language for Specific Purposes (LSP) curriculum that would help them learn ‎a closed set of ‎syntactic rules ‎and ‎‎vocabularies in the ‎context ‎of the Qur'an, so that they can recall an idiomatic translation in their native language while they recite or listen to the Qur'an. Little research work exists on the user modeling and needs analysis for this purpose. In this paper, ‎the design and initial ‎prototype of a ubiquitous web-based ‎language learning software founded on the ‎LSP principles is presented and some ‎initial results of need analysis of the user data are shared. The preliminary results of ‎this study indicate the potential of this approach and highlight the areas where ‎improvement is required.